Dynamic Responses of Inflation, Agricultural Production, and Terms of Trade to Oil Price Fluctuations in Kazakhstan: An Structural VAR Approach - Yesbolova, Ainur Yergazievna; Abdikerimova, Gulzhanar I.; Naribek, Bagdaulet; Sarkulova, Nursulu; Mukhan, Bakytzhan S.; Kulanova, Darikul; Bolganbayev, Artur (International Journal of Energy Economics and Policy, 2025)
The influence of oil price fluctuations on Kazakhstan’s inflation, agricultural production, and terms of trade over 2000-2024 is examined using annual observations for 2001-2024. A Structural VAR with recursive long-run (F-triangular) identification is estimated, and a VAR(4) specification is selected by LR, FPE, AIC, and HQ criteria. Results indicate moderate inflation persistence and pronounced agricultural inertia, while net trade dynamics are primarily autoregressive. Structural estimates and impulse responses show that positive oil price shocks raise inflation in the short run and temporarily depress agricultural production, with effects fading over the medium term; trade shocks briefly lift inflation, whereas inflation shocks modestly weaken net trade. Variance decompositions confirm that inflation is predominantly self-driven (≈85.5% at a ten-period horizon) but increasingly influenced by oil and supply-side conditions; agricultural output displays rising sensitivity to inflation and trade signals; oil prices remain largely exogenous with limited domestic feedback. Policy implications include stronger fiscal-monetary coordination to contain oil-induced inflation, productivity and energy-efficiency gains in agriculture to cushion cost shocks, and export diversification to mitigate terms-of-trade volatility and enhance macroeconomic resilience.